Endodontic Treatment Of Upper First Premolar With 3 Canals- Case Report - Khan, Dania; Ahmed, Alia; Haq, Sabana; Sajid, Khadija; Rizwan, Zarnab; Zahid, Aqsa (Journal of Rawalpindi Medical College, 2024)
A comprehensive understanding of the root structure is important for the successful outcome of endodontic procedures. Lack of knowledge of the anatomic variations in root canal morphology can contribute to the failure of root canal therapy. One of the most anatomically diverse tooth groups is the upper first premolar. The incidence of two root canals is the most predominant anatomy observed for maxillary first premolar however some anatomical variations are also observed. The most frequent anatomical variation in these teeth is the existence of three roots with three canals. The objective of this study is to report a similar case of maxillary first premolar having three roots with separate 3 canals. Endodontic success requires a thorough understanding of root canal anatomy. The variation in the number of roots, canals, root direction, longitudinal depressions of the roots, the various shapes of the pulp cavity and the problems in visualizing the apical limit by radiographs make the endodontic procedure of these teeth quite challenging.